2022
DOI: 10.3389/fenvs.2022.922151
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment entry mode and China’s carbon productivity based on spatial econometric model

Abstract: As the world’s largest developing country and the largest carbon emitter, China must consider economic growth and carbon emission reduction in development. Therefore, improving carbon productivity is an important goal of China at present. At the same time, China’s foreign capital inflow has always been at the forefront of the world, and foreign direct investment (FDI) has had various impacts on China’s carbon productivity. Based on the panel data of 25 provinces in China from 2007 to 2019, this paper uses a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…(5) Industrial structure (ins) is represented by the proportion of the gross value of the secondary industry to the regional gross value of production (Tang et al 2022).…”
Section: Control Variablementioning
confidence: 99%
“…(5) Industrial structure (ins) is represented by the proportion of the gross value of the secondary industry to the regional gross value of production (Tang et al 2022).…”
Section: Control Variablementioning
confidence: 99%
“…Hence, the CP of a province helped to increase CP in neighboring provinces. Tang et al (2022) examined 25 Chinese provinces from 2007–2019 and found that FDI in terms of joint ventures had positive direct and spillover effects. However, FDI in a completely foreign-owned firm carried the opposite effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the macro country level, Liu et al [ 15 ] introduce panel threshold regression models to investigate the OFDI–green innovation relationship of China from the home country’s perspective and decompose the relationship into scale, composition, and technique effects. Li et al, Zhang et al and Tang et al [ 56 , 57 , 58 ] theoretically analyze and empirically test the impact of OFDI on the home country’s global value chain upgrading. Luo et al [ 59 ] claim that OFDI might lead to massive investment and a long-term investment cycle, given the total financial constraints; this may, in turn, decrease the R&D investment of a certain company, thus, hindering the green innovation activities of the enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%